2020
DOI: 10.3390/su12208728
|View full text |Cite
|
Sign up to set email alerts
|

Key Indicators for Linguistic Action Perspective in the Last Planner® System

Abstract: Since 2001, a link has been established between the Last Planner® System (LPS) and Linguistic Action Perspective (LAP). However, to date, it has not been studied in sufficient depth. This research developed a system of indicators to measure and control the management of commitments, through the Design Science Research (DSR) methodology, and thus contribute to the development of the social dimension of sustainability that is often neglected in construction management research. The main contributions of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Recently and as part of a pandemic labour reactivation strategy, the company began to make use of the "Engagement" indicators proposed by Salazar et al (2020), in order to control and improve interpersonal relationships at work and engagement during weekly work planning meetings.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently and as part of a pandemic labour reactivation strategy, the company began to make use of the "Engagement" indicators proposed by Salazar et al (2020), in order to control and improve interpersonal relationships at work and engagement during weekly work planning meetings.…”
Section: Methodsmentioning
confidence: 99%
“…When reviewing the Web of Science database, the authors found four articles regarding "Linguistic Action Perspective" or "Language Action" in construction projects (Isatto et al 2015;Salazar et al 2020;Viana et al 2017;Zegarra and Alarcon 2017). However, from these studies, including the countless IGLC publications (Howell et al 2004;Long and Arroyo 2018;Viana et al 2011;Zegarra and Alarcón 2013), there is only one proposal for LAP indicators (Salazar et al 2018(Salazar et al , 2019(Salazar et al , 2020, but it does not explain the relationship between how these commitments are established and the outcome. In addition, only partial results of the relationship between some LAP indicators, Percentage Plan Completed (PPC) and Social Networks are shown in the publication of Retamal et al (2020).…”
Section: State Of the Art And Practicementioning
confidence: 99%
See 3 more Smart Citations